Review Jembatan Sutami di Bandar Lampung - Akhmad Dendi Nosya; Fikri Alami; Surya Sebayang (Jurnal Rekayasa Sipil dan Desain, 2018)
Many structural systems are available to build a bridge. One of them is prestressed concrete bridge. The purpose of this research is to review the design of prestressed concrete bridge using SAP 2000 ver. 14 software.This research use elastic method on prestressed concrete, and ultimate method on the design of the other structures on the bridge. Whereas finite element analysis (FEA) with SAP 2000 ver.14 is used on traffic load analysis . From the analysis results, the longitudinal girder requires bending reinforcement of 12 D13, skin reinforcement of 6 ∅13, and 18 strand with dia. of 0.5" in each tendon. There is a difference with existing design which use bending reinforcement under the minimum requirement, whereas the strand used, meets the recent code.Slab requires bending reinforcement of ∅16-200, shrinking reinforcement and temperature of ∅13-250, however the existing design used denser reinforcement, this difference is due to changes in the bending reduction factor which follows the recent code of 2013 .Diaphragms requires bending reinforcement of 2 D28, skin reinforcement of 5 ∅13, and shear reinforcement of ∅13-500. this difference is due to changes in the reduction as well. Whereas in the shear reinforcement used by the existing design has met the recent code.Barrier wall requires bending reinforcement of ∅19-150 for the thickening area below the wall, ∅13-150 for the above area, and shear reinforcement of 10 ∅13, thus the reinforcement used by the existing design has met the recent code. The conclusion that can be taken is that the reinforcement used for the main structure component is correct, but some bending reinforcement are used under the need of ρmin and concrete standard of 2013. Keyword : bridge, prestressed concrete, SAP 2000 ver. 14